2020
DOI: 10.1108/ajar-07-2020-0061
|View full text |Cite
|
Sign up to set email alerts
|

Empirically examining the impact of corporate social responsibility on financial performance: evidence from Indian steel industry

Abstract: PurposeThis paper aims to examine the impact of corporate social responsibility (CSR) on financial performance (FP) of Indian steel industry in terms of value-added (VAM), profitability (PM), market (MM) and growth measures (GM).Design/methodology/approachIt is an empirical study using secondary data of 40 companies for 14 years collected from CSR/annual reports/official websites of the companies and Prowess database. The panel regression analysis, MANOVA and univariate ANOVA have been conducted to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
1
10
0
5
Order By: Relevance
“…Still, studies (Margolis et al, 2009; Orlitzky et al, 2003; Wang et al, 2016) found weak and vague results. The multiple definitions of CSRD, that is, unidimensional (Kaur & Singh, 2020; Maqbool & Bakr, 2019) and multidimensional (Usman & Amran, 2015; Wang et al, 2014; Zhu et al, 2016) by academicians made the linkage inconclusive. Also, Orlitzky et al (2003) stated the findings of the relationship of CSRD and FP cannot be generalized to all the dimensions of CSRD.…”
Section: Introductionmentioning
confidence: 99%
“…Still, studies (Margolis et al, 2009; Orlitzky et al, 2003; Wang et al, 2016) found weak and vague results. The multiple definitions of CSRD, that is, unidimensional (Kaur & Singh, 2020; Maqbool & Bakr, 2019) and multidimensional (Usman & Amran, 2015; Wang et al, 2014; Zhu et al, 2016) by academicians made the linkage inconclusive. Also, Orlitzky et al (2003) stated the findings of the relationship of CSRD and FP cannot be generalized to all the dimensions of CSRD.…”
Section: Introductionmentioning
confidence: 99%
“…Content analysis has been applied for the data extraction. For each of these 12 activities, Score 1 is allotted if a specific activity has been disclosed and Score 0 is allotted in case of non-disclosures (Kaur and Singh, 2021). These scores have been converted into rating using the following formula: …”
Section: Methodsmentioning
confidence: 99%
“…There is no consensus on measuring financial performance (Kaur & Singh, 2021;Maqbool & Zameer, 2018). Our study relied on three indexes: return on assets, return on equity, and earnings per share.…”
Section: Corporate Financial Performance As Dependent Variablementioning
confidence: 99%
“…We found that the availability of knowledge and skill among corporate managers on boards is positively correlated with improvements in CSR performance; In addition, its positive impact automatically reflects on the corporate financial performance. As a result, rather than treating CSR as a stand-alone activity, executives should integrate it into their overall company plan(Kaur & Singh, 2021) Dobers and Halme (2009). draw attention to a number of CSR problems in emerging nations.…”
mentioning
confidence: 99%